A conceptual model for the E-commerce application recommendation framework using exploratory search - Mohammed Mahmudur Rahman; Zulkifly Mohd Zaki; Md. Monirul Islam; Najwa Hayaati Mohd Alwi (Science Publications, 2024)
Indexed by Scopus/ERA